The principles of quantum mechanics [4th ed.] - Dirac, P. A. M. (Oxford Oxford University Press, 1958)
Principles of Quantum Mechanics is a comprehensive book for undergraduate students of Mechanical Engineering. The book comprises chapters on dynamical variables and observables, the quantum conditions, the equations of motion, perturbation theory, collision problems, theory of radiation, the relativistic theory of the electron, and quantum electrodynamics. In addition, the book consists of several examples and equations to understand the complex concepts of quantum mechanics better. This book is essential for researchers and advanced students of quantum theory.
Keywords: Matrix mechanics; Quantum theory